Correlation between Insulin Resistance with Soluble CD40 Ligand and Plasminogen Activator Inhibitor-1 Plasma in Pre-diabetic Patients - Decroli, Eva; Afriant, Rudy; Kam, Alexander; Puspita, Upi (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: The main condition of pre-diabetes is insulin resistance that can lead to a prothrombotic state. AIM: This study aims to correlate insulin resistance with soluble CD40 ligand (sCD40L) and plasminogen activator inhibitor-1 (PAI-1) plasma in pre-diabetic patients. METHODS: This study is an analytic observational study with a cross-sectional approach. HOMA-IR assessed insulin resistance, and prothrombotic factors were assessed by PAI-1 and soluble CD40L. PAI-1 and sCD40L were examined by ELISA. These indicators were assessed on 30 pre-diabetic patients. RESULTS: Thirty subjects included in this study with a mean age of 31.47 (5.03) years old, consist of 19 (63%) men and 11 (37%) women. The mean HOMA-IR was 3.69 (1.12), PAI-1 was 10.25 (3.72) ng/mL, and the PAI-1 levels were increased (>8.4 ng/mL) in 70% of the subjects. The mean of sCD40L levels was 4495.7 (1136.3) pg/ml, and sCD40L levels were increased (>4000 pg/ml) in 63% of subject. There was a significant correlation between HOMA-IR levels and sCD40L (r = 0.636, p < 0.05) and between of HOMA-IR and PAI-1 (r = 0.742, p < 0.05). Moderate correlation was found between sCD40L levels and plasma PAI-1 (r = 0.592, p < 0.05) in pre-diabetic patient. The correlation between three variables was HOMA-IR had a significant effect on PAI-1 levels through sCD40L (t = 2.010, p < 0.05, structure loading factor = 0.286). CONCLUSION: Insulin resistance has a strong and significant correlation with sCD40L and PAI-1 levels in pre-diabetic patients.